Multimodal ex vivo methods reveal that Gd-rich corrosion byproducts remain at the implant site of biodegradable Mg-Gd screws. (December 2021) - Peruzzi, Niccolò; Galli, Silvia; Helmholz, Heike; Kardjilov, Nikolay; Krüger, Diana; Markötter, Henning; Moosmann, Julian; Orlov, Dmytro; Prgomet, Zdenka; Willumeit-Römer, Regine; Wennerberg, Ann; Bech, Martin
Abstract: Extensive research is being conducted on magnesium (Mg) alloys for bone implant manufacturing, due to their biocompatibility, biodegradability and mechanical properties. Gadolinium (Gd) is among the most promising alloying elements for property control in Mg alloy implants; however, its toxicity is controversial. Investigating Gd behavior during implant corrosion is thus of utmost importance. In this study, we analyzed the degradation byproducts at the implant site of biodegradable Mg-5Gd and Mg-10Gd implants after 12 weeks healing time, using a combination of different imaging techniques: histology, energy-dispersive x-ray spectroscopy (EDX), x-ray microcomputed tomography (µCT) and neutron µCT. The main finding has been that, at the healing time in exam, the corrosion appears to have involved only the Mg component, which has been substituted by calcium and phosphorus, while the Gd remains localized at the implant site. This was observed in 2D by means of EDX maps and extended to 3D with a novel application of neutron tomography. X-ray fluorescence analysis of the main excretory organs also did not reveal any measurable accumulation of Gd, further reinforcing the conclusion that very limited or no removal at all of Gd-alloy happened during degradation. Statement of significance: Gadolinium is among the most promising alloying elements for property control in biodegradable magnesium alloy implants, but its toxicity is controversial and its behavior during corrosion needs to be investigated. We combine 2D energy dispersive x-ray spectroscopy and 3D neutron and x-ray tomography to image the degradation of magnesium-gadolinium implants after 12 weeks of healing time. We find that, at the time in exam, the corrosion has involved only the magnesium component, while the gadolinium remains localized at the implant site. X-ray fluorescence analysis of the main excretory organs also does not reveal any measurable accumulation of Gd, further reinforcing the conclusion that very limited or no removal at all of Gd-alloy has happened during degradation. Graphical abstract: Image, graphical abstract